The banquet in Etruscan funerary art and its underlying meaning - Mitterlechner, T (2010)
The motif of the banquet plays an important role in Etruscan sepulchral art from 7th - 1st century BC. The theme is found in Etruscan tomb painting, funerary reliefs and funerary sculpture. While there is no doubt about the importance of the theme in Etruria, its meaning is open to debate. Do the images represent banquets connected to the funerary-ritual, do they show a banquet of the blessed in the netherworld, or do they depict characteristic moments of an upper-class life? In any case, the Etruscan banquet-imagery has to be understood in terms of self-representation. The images also experience a change in their underlying meaning: the earliest images showing a single banqueting figure may be interpreted in terms of heroising the dead. Representations in tomb-painting of the late sixth and fifth centuries BC, however, are more likely to show real-life banquets which can be deduced from the combination of the banquet motif itself with other imagery (athletic and music contests, dance etc.). The owners of the tombs represent themselves on equal terms together with other participants of the banquet. In the late fifth century BC, another shift of meaning occurs, as some of the banquets in Etruscan tomb-painting clearly take place in the afterlife: dark clouds surround the deceased who eat and drink together with their ancestors. The presence of underworld-demons or the rulers of the netherworld stresses the otherworldly character of the scenes. In these images, the aspects of heroisation and the glorification of the family gains in importance, as can also be inferred from long inscriptions honouring the dead and their deeds. This contribution will trace the evolution of the banquet motif in Etruria especially with regard to its underlying meaning.